The Main Characteristics of Dialogic Interaction (Defining the Actual Tasks of Pedagogic Dialog - Y. V. Yermolayeva (Образование и наука)
The paper deals with one of the fast developing modern educational approaches – the pedagogy of dialog, based on the philosophical works and concepts of the well-known thinkers of the 20-th century: M. Buber, F. Ebner, O. Rosenshtok-Hussy, M. Bakhtin, etc. Two main directions of dialogic pedagogy are outlined – the instrumental and ontological. Within the framework of the first direction, the dialog is considered to be the main means or instrument of effective teaching used for communication skills development. According to the ontological version, the dialog is not only the instrument, but rather the dominating goal of education: it facilitates meaning- ful assimilation of skills and knowledge, including the learning ability; promotes cooperation and communal life skills; provides favorable conditions for versatile creative self-development. The supporters of this approach regard the real people, as well as the art works, nature, culture, alter ego etc, as the dialog subjects. The paper observes the main characteristics or prerequisites of dialogic interaction: dialogic attitude (emotionally ethical precondition); antinomian thinking (intellectual precondition); open outlook and creativity (precondition of personal meaning creation in the course of dialog). The comparative analysis of dialogism and non-dialogism of schoolchildren from Riga and Moscow are given regarding their behavior in conflicting situations; attitude to extremism; and reactions to bulling situations. The author is convinced that studying students’ dialogism in different age groups should be continued to improve the educational process effectiveness. Shearing the positive experience in dialogic education by Latvian and Russian colleagues can be very useful.